Analysis of the oxidized surface of 90Nb-10Zr alloy after exposure to lithiated water with 0.01 M LiOH at 360 °C/18.6 MPa. (March 2016) - Huang, J.; Yao, M.Y.; Gao, C.Y.; Hu, P.F.; Liang, X.; Zhang, J.L.; Zhou, B.X.; Li, Q.; Ahsan, E.
Highlights: Adopt 90Nb–10Zr alloy similar to β-Nb in zirconium alloys to avoid effect of α-Zr. New insight into the oxidation process of 90Nb–10Zr alloy is provided. The dissolution of Nb2 O5 on 90Nb–10Zr alloy in lithiated water is observed. A degradation mechanism on Zr–1Nb alloy corroded in lithiated water is proposed. Abstract: The microstructural characteristics of oxide films on 90Nb–10Zr (wt%) alloy in lithiated water were investigated to understand the oxidation process of β-Nb precipitates in Zr–1Nb (wt%) alloy. The outer layer of the alloy is faceted, and has loosely packed LiNbO3 particles. Pores and nano-sized LiNbO3 are present between the outer and the compact Nb2 O5 inner layer. Nb2 O5 reacted with LiOH to form LiNbO3 and it dissolved into the corrosive environment to leave pores in the oxide films. The Zr oxidised and dissolved in Nb2 O5 . A degradation mechanism is proposed on the corrosion resistance of the Zr–1Nb alloy in lithiated water.